Diuretic Effect and Metabolomics Analysis of Crude and Salt-Processed Plantaginis Semen - Chao Li; Rou Wen; De Wen Liu; Qiang Liu; Li Ping Yan; Jian Xiong Wu; Yi Jing Guo; Su Yun Li; Qian Feng Gong; Huan Yu (Frontiers Media S.A., 2020)
Plantaginis Semen (PS) is well recognized in traditional Chinese medicine (TCM) and health products. Crude PS (CPS) and salt-processed CPS (SPS) are the two most commonly used decoction pieces of PS, and are included in the 2020 edition of Chinese Pharmacopoeia. Although they all have multiple effects, the mechanisms for treating diseases are different and remain unclear, the processing mechanism of SPS is also indeterminate, which hinders their clinical application to a certain extent. In order to solve these problems and further develop PS in the clinical application. Here, we used saline-loaded model rats for experiments, and utilized an integrated approach consisting of pharmacological methods and metabolomics, which could assess the diuretic impact of CPS and SPS ethanol extracts on saline-loaded rats and elucidate the underlying mechanism. The results showed that CPS and SPS both produced increased urine volume excretion and urine electrolyte excretion, but the levels of aldosterone (ALD) and aquaporin 2 (AQP2) were decreased. And 30 differential metabolites such as linoleic acid, lysoPC(O-18:0), sphingosine-1-phosphate, lysoPC(18:0) were found, mainly involving three metabolic pathways. In conclusion, CPS and SPS both have a diuretic effect, and that of SPS is better. This work investigated the possible diuretic mechanisms of CPS and SPS which may also be the mechanism of PS for anti-hypertension. In addition, a holistic approach provided novel and helpful insights into the underlying processing mechanisms of TCM.